Italian Liberal Imperialism in China: A Review of the State of the Field. Issue 12 (December 2013) - Urosevic, Uros
Abstract The story of Italian imperialism in China is an almost forgotten one. Few know that the Kingdom of Italy was on the verge of war with the Qing Empire in 1899 and that, following its participation in the Boxer War a year later, it acquired a concession in Tianjin, which it kept until 1947. This nearly forgotten episode is important, however, for understanding Italian imperialism as a whole. For a number of years, research of Italian imperialist past has tended to pay more attention to fascist imperialism at the expense of liberal imperialism, at times making Italian imperialism in general appear as an outgrowth of fascism. This is dangerously misleading, as it was imperialism of the liberal era that first revealed expansionistic tendencies that would characterise Italian fascism half a century later. The historical importance of Italian liberal imperialism as a precursor of fascist imperialism and an important early signal of totalitarian proclivities of Italian political elites needs, therefore, to be critically reappraised.